POTENSI PENGGUNAAN QUICK RESPONSE CODE INDONESIAN STANDARD (QRIS) UNTUK MENINGKATKAN INKLUSI KEUANGAN MIKRO DI WILAYAH OGAN KOMERING ULU MELALUI BANK BSI KC BARURAJA RAHMAN HAMIDI - Erlangga, Dimas Bayu; Retnosari, Retnosari (Mount Hope Management International Journal, 2025)
The times and technological developments also occur in financial institutions. One technology that has a lot of potential in developing the financial sector in Indonesia is QRIS. QRIS is a QR code-based payment system that complies with Indonesian standards. QRIS has access to all digital wallets and all banks to facilitate all types of transactions. The type of research used in the implementation is a qualitative method. Qualitative methods are carried out to be able to find out the phenomena that are happening in certain areas and are being experienced by research subjects. The use of QRIS at Bank BSI KC Baruraja Rahman Hamidi also facilitates community access to all people. This condition can occur because the use of QRIS can receive and send money through all applications, both mobile banking and digital wallets.